Fraud in Land Dealings in Malaysia: A Study: (Penipuan dalam Urus Niaga Tanah di Malaysia: Satu Kajian) (Kanun: Jurnal Undang-undang Malaysia, 2022)
This article was written to examine the issue of land fraud arising from land dealings in Malaysia. Various types of modus operandi have been committed by criminals in this fraud. With these modus operandi, many land offices have been successfully deceived into causing fraudulent land dealings. This has triggered concerns in the public about the legal surety of their proprietorship, which should be legally indefeasible upon legal registration in accordance with the National Land Code (NLC). The study conducted is based on analysis of cases that have been decided by the courts. The findings showed that various types of modus operandi (MO) were attempted by fraudsters and there were various factors that led to the commission of such fraudulent acts. This paper also highlights several suggestions for improvement in order to curb attempted frauds in land dealings.Keywords: Fraudulent land dealing, identity fraud, proprietorship, case analysis, modus operandi, transactionFull text: PDF